Synthesis of textured discontinuous-nanoisland Ca3Co4O9 thin films. Issue 16 (13th July 2022) - Xin, Binbin; Le Febvrier, Arnaud; Lu, Jun; Paul, Biplab; Eklund, Per
Abstract : Discontinuous films with islands of highly textured Ca3 Co4 O9 effectively constituting distributed nanoparticles can be obtained by controlling the Ca/Co ratio. Abstract : Controllable engineering of the nanoporosity in layered Ca3 Co4 O9 remains a challenge. Here, we show the synthesis of discontinuous films with islands of highly textured Ca3 Co4 O9, effectively constituting distributed nanoparticles with controlled porosity and morphology. These discontinuously dispersed textured Ca3 Co4 O9 nanoparticles may be a candidate for hybrid thermoelectrics.